Euroland: recovery is under way - Klaus-Jürgen Gern; Christophe Kamps; Joachim Scheide (Institut für Weltwirtschaft (IfW), 2002)
The economy in the euro area has turned around. While GDP stagnated during the second half of 2001, there are more and more signs that output will increase considerably in the first half of this year. All in all, the slowdown has not been very pronounced. One indication for this is that in 2001, the year of the downturn, unemployment remained more or less constant. The factors which led to the cyclical slowdown have turned around and now stimulate economic activity: Monetary policy has become expansionary, oil prices have dropped substantially, and there is a recovery in the rest of the world. Key interest rates in the euro area have remained unchanged since early November 2001. Real short-term interest rates are well below their historical average. Therefore, economic activity is stimulated by monetary policy. Until spring 2003, the ECB will raise key interest rates to the neutral level which should prevail when the output gap is closed and when inflation is at its target; this neutral rate lies between 4 and 4.5 percent. Money growth has exceeded the reference value of 4.5 percent for M3 considerably for several months. This increase implies that the velocity of money shows an unusually large deviation from its trend. According to the judgment of the ECB, the demand for M3 has become unstable only in the short run due to special factors. If this judgment is correct, money growth will slow down markedly in the coming months. As a consequence, velocity will return to its trend without an increase in inflation. This implies, however, that the expected slowdown of money growth should not be used as an indication that monetary policy is tight and needs to be loosened because the deceleration of M3 growth is nothing but a normalization. Fiscal consolidation has been insufficient in several countries. Governments in Germany, France, Italy and Portugal should begin to pursue a strict consolidation course. Empirical evidence shows that countries that undertook credible consolidation strategies based on expenditure cuts did not experience cyclical downturns. If the governments of these countries were to dampen the increase in government spending, there would be room for a reduction of the tax burden and of budget deficits. This would improve the growth perspectives for the medium term. In 2001, wages in the euro area increased somewhat faster than in the previous years largely reflecting the improvement of the labor market situation due to the strong upswing. Also, employees tried to limit the reduction of real wages, which was the consequence of the higher than expected rate of inflation. In our forecast, wage increases will average about 3 percent both this year and next. This implies that there is room for an increase in employment although it is smaller than at the end of the 1990s. Nevertheless, the development of wages does not imply a risk for price level stability. The leading indicators suggest that the European economy has reached its trough in the first quarter of 2002 and that the upswing is imminent. From spring on, real GDP will increase at a faster pace than potential output. On average, it will increase by 1.7 percent in 2002. In the course of the coming year, the increase in production will gradually slow down. The upswing in the world economy will probably pass its peak in the first half of next year implying a less dynamic external demand for European products. Domestic demand will also lose some momentum. This is due to the fact that monetary policy will return to a neutral course and that the effects of the preceding easing will gradually fade. We expect real GDP to increase by 3 percent in 2003.
Keywords: 330; Konjunktur; Konjunkturprognose; Europäische Wirtschafts- und Währungsunion; EU-Staaten